Government Ecology Contribution to Realizing Competitive Local Government Policies - Bayu Karunia Putra; Azizatul Farhaini; Dinatul Aini; Siti Nurjannah; Noviana Noviana; Linda Tuanida Ningrum; M Yusron Azzahidi (Peneliti.net, 2023)
This article aims to determine the ecological contribution of government to realize competitive local government policies. Topic is important and interesting, because the governance ecology is part of the basis for making a policy, in addition to being a leading reference in the preparation of government policies, as well as being a digital tool that transforms all activities directly related to the process of administering government which aims to increase effectiveness, efficiency, and create maximum policy. The research method used is the literature review method, in which sources and data are obtained through the Publish or Perish, SINTA, and Goggle Scholar databases. In this method, researcher uses a descriptive qualitative approach, in which this method utilizes qualitative data and is described descriptively. Data collection techniques use literature review techniques carried out by researchers to collect valid, complete, and relevant information related to the topic of the problem which is the object of research. The data analysis technique used a literature review analysis technique, in which this research was conducted by reading literary sources to obtain the necessary data. The author found that, local government policies will be more effective and efficient, when policies are carried out in policy formulation based on governance ecology, local governments seek to have competitiveness by sticking to commitments in carrying out local government processes, and the process of increasing competitiveness has improved with increased knowledge and ability of apparatus in public service that has been optimal.